Sex identification by maxillary sinus measurements using MDCT : a study among Malay adults in Hospital Universiti Sains Malaysia (HUSM) - Muhamad Nor, Siti Noorul Arisah (2015)
Background: Sex identification of the skeletal remains is one of the concerns in forensic medicine, apart from age, stature and race. Since most bones that are conventionally used for sex determination are often recovered either in a fragmented or incomplete state, it is necessary to use denser bones that are often recovered intact, for example maxillary sinus. Nowadays, the introduction of Multidetector Computed Tomography (MDCT) with thin axial sections, sagittal and coronal reformatted images has allowed a more accurate assessment of this structure. Apart from the difficulty in obtaining a complete skeleton for sex identification, the variable parameters measured are population specific. Thus, the aim of this study is to evaluate the accuracy of maxillary sinus measurements by MDCT in identification of sex among adult Malay population attending Hospital Universiti Sains Malaysia (HUSM). Objective: To determine the sex by measurement of maxillary sinus dimensions using MDCT in Malay adults. Methodology: This was a cross-sectional study done at the Department of Radiology, HUSM from November 2011 until November 2014. MDCT scan study for head trauma of 140 adult Malay patients aged between 18 to 89 years were reviewed. Ten maxillary sinus dimensions were measured and subjected for descriptive and univariate/multivariate discriminant function analysis. Data entry and analysis were performed using Statistical Package for Social Sciences (SPSS version 22) software programme. Results: Our results showed statistically significant difference of the mean value of maxillary sinus dimensions in males and females. The mean values for males were consistently higher as compared to females. Eight out of 10 measurement parameters taken in this study were significant for sex identification except for total distance across both sinuses and intermaxillary distance. The accuracy of sex determination by maxillary sinus dimensions using univariate discriminant function analysis is ranging from 61.5% to 67.9%. Our study also showed that combination of two or more measurement parameters using multivariate discriminant function analysis has increased the accuracy in sex identification by maxillary sinus dimensions with the highest accuracy of 70.7% for the right maxillary sinus. Conclusion: Measurement of maxillary sinus dimensions by multidetector computed tomography (MDCT) is useful for gender differentiation among Malay adults and fairly accurate for sex identification in Forensic Medicine.